Description of the immature female instars of Ceroplastes rusci (Linnaeus) (Hemiptera: Coccidae) - Pellizzari, Giuseppina; Rainato, Alessio; Stathas, George J. (Zootaxa, 2010)
The immature female instars of the fig wax scale, Ceroplastes rusci (L.), are redescribed and illustrated here with the aim of improving our knowledge on its morphology and phenology by the correct identification of the pest stages present on the host plant. A key to different instars is also provided. The biology of this species, which has recently increased in abundance in fig cultivation areas in Messinia (Greece), is briefly discussed.